Abortion in Modern America: The Influence of the Legal, Religious, Political Factors in Changing Attitudes - BEKRI, HADIL BELKIS (My University, 2023)
Abortion is a highly controversial topic that has been debated for decades, both in the United States and around the world. It involves the termination of a pregnancy by removing a fetus or embryo from the uterus before it can survive outside the womb. with many people holding strong opinions on both sides of the issue. There are deep questions about morality, ethics, and the law that are central to this debate. In the United States, the current situation of abortion is complex and varies widely depending on each state. The landmark Supreme Court decision in Roe v. Wade in 1973 legalized abortion nationwide, but since then, states have enacted a patchwork of laws that regulate access to abortion due to the backlash against the law. In recent years, there has been a renewed effort to ban abortion or restricted after a certain point in pregnancy. This study pursues to highlight how the legal status of abortion has shifted from being recognized as a constitutional right to being severely restricted in many parts of the country. The debate over abortion in the United States is unlikely to be resolved anytime soon. It is a deeply personal issue that involves a woman's right to make decisions about her own body and the potential life of a fetus. As such, it is likely to continue to be a source of controversy and debate for many years to come.
Keywords: Abortion; morality; law; Roe v. wade; controversy; debate; Constitutional right; US